Monkeypox Virus (MPXV): Epidemiology, Pathogenesis, and Control Strategies: Exploring the Recent Resurgence of Monkeypox, Its Transmission Dynamics, Clinical Manifestations, and Public Health Responses - Tahseen Khan (International Journal of Virus Studies, 2025)
Monkeypox virus (MPXV) has re-emerged as a significant public health concern, with increasing cases reported worldwide. This zoonotic virus, primarily endemic to Central and West Africa, has demonstrated the potential for human-to-human transmission, leading to outbreaks in non-endemic regions. Unlike smallpox, which was eradicated through mass vaccination, monkeypox continues to persist due to the lack of widespread immunity and effective antiviral treatments. The resurgence of MPXV in recent years, particularly in non-endemic regions, underscores the urgent need for improved surveillance, vaccination strategies, and public health interventions. This review provides a comprehensive analysis of the epidemiology, pathogenesis, transmission dynamics, clinical manifestations, and public health responses associated with monkeypox. The epidemiology of MPXV highlights the virus's expanding geographical distribution, with increased outbreaks reported across continents due to global travel and environmental changes. The pathogenesis of MPXV is explored, focusing on its mechanisms of infection, immune evasion strategies, and the host immune response. Clinical manifestations vary from mild to severe, with complications such as secondary infections, pneumonia, encephalitis, and ocular involvement in some cases. Furthermore, this review examines transmission dynamics, including zoonotic spillover, human-to- human transmission, and environmental persistence. Public health responses, including vaccination campaigns, treatment protocols, and community awareness programs, play a crucial role in controlling outbreaks. Although vaccines such as JYNNEOS and ACAM2000 offer protection, challenges remain regarding vaccine accessibility and public acceptance. The role of antiviral treatments such as Tecovirimat (TPOXX) is also discussed, emphasizing the need for further clinical research. Finally, the review highlights future challenges, including the potential for viral mutations, disparities in healthcare infrastructure, and the need for global cooperation in combating MPXV. By understanding the epidemiology, pathogenesis, and transmission dynamics of monkeypox, this review aims to provide insights into effective control measures and preparedness strategies for future outbreaks. Strengthening surveillance, investing in research, and enhancing global collaboration will be key to mitigating the impact of MPXV in the years to come.
Keywords: Accessibility; Antiviral; Immune; Surveillance; Zoonotic